2022
DOI: 10.1093/brain/awac136
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing ibudilast to mitigate Alzheimer’s disease by targeting inflammation

Abstract: Alzheimer’s disease is a multifactorial disease that exhibits cognitive deficits, neuronal loss, amyloid plaques, neurofibrillary tangles and neuroinflammation in the brain. Hence, a multi-target drug would improve treatment efficacy. We applied a new multi-scale predictive modeling framework that integrates machine learning with biophysics and systems pharmacology to screen drugs for Alzheimer’s disease using patient’s tissue samples. Our predictive modeling framework identified ibudilast as a drug with repur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Understanding pre- and/or early-stages of AD is paramount, as treating AD at these stages would be the best approach to preventing severe progression ( Sun et al, 2018 ). We established that at 11 mo of age, the Tg-AD rats exhibit impaired hippocampal-dependent spatial learning and memory, as well as molecular markers of AD, such as amyloid plaques, microglial activation, neuronal loss, and early signs of τ-PHF, the latter reported by us ( Oliveros et al, 2022 ).…”
Section: Discussionmentioning
confidence: 56%
“…Understanding pre- and/or early-stages of AD is paramount, as treating AD at these stages would be the best approach to preventing severe progression ( Sun et al, 2018 ). We established that at 11 mo of age, the Tg-AD rats exhibit impaired hippocampal-dependent spatial learning and memory, as well as molecular markers of AD, such as amyloid plaques, microglial activation, neuronal loss, and early signs of τ-PHF, the latter reported by us ( Oliveros et al, 2022 ).…”
Section: Discussionmentioning
confidence: 56%
“…Recently, neuroinflammation has been recognized to play a predominant role in AD etiology and can be a potential AD drug target [ 59 ]. We have shown that anti-inflammation agent ibudilast can mitigate AD in the transgenic AD rat model [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…and can be a potential AD drug target [59]. We have shown that anti-inflammation agent ibudilast can mitigate AD in the transgenic AD rat model [60].…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Might broadly anti-inflammatory agents targeting microglia also be used as putative HAND therapeutics? microglia [53], such as the phosphodiesterase inhibitor ibudilast [54], could be explored as potential complementary strategies to treat HAND.…”
Section: Outstanding Questionsmentioning
confidence: 99%